FEATURES OF THE FORMATION AND DEVELOPMENT OF TRANSLATION COMPETENCE IN THE PROFESSIONAL ENGLISH COURSE (Education in the 21st Century, 2022)
The corresponding analysis shows that the application of a competent approach allows translators and   theorists of teaching translation theory to adopt new technologies and methods in the process of teaching translation. However, some researchers are convinced that bilinguals can do translations and it is not advisable to form translation competence in educational conditions. There are also those approaches according to which translation competence is a manifestation of a kind of super-competence, in the sense that translation involves mental activity and includes conscious and unconscious processes. Basically, researchers are unanimous in the opinion that the basis of translation competence is language, linguistic, pragmatic, cultural, socio-cultural and other competencies that form the basis of communicative competence. From the point of view of teaching translation, cultural and technical competencies stand out. A positive trend is that translation theorists and methodologists have clearly begun to distinguish between translation competence and the competence of teaching translation. It is fundamentally important to develop literary competence, which is necessary at the stage of pre-translation analysis and at the stage of translation.It is impossible to imagine translation competence without the development of communicative competence, since the translator must be able to determine the transmitted information as correctly and purposefully as possible in different speech situations. The translator must be psychologically well prepared, mentally flexible and inquisitive. He/she must read a huge number of fiction or other genres of literature. In intercultural terms, he must be patient, indulgent. He must be able to use various translation and learning strategies.Thus, the challenge is to apply new strategies, methods and procedures. It is noteworthy that within the framework of theories of learning and translation, not only translation strategies are developed, but also macro and micro strategies.
Keywords: literary competence; strategic competence; communicative, pragmatic, intercultural, language competence